Design of an integrated management system (IMS) in a government-run medical evaluation organisation. Issue 6 (7th October 2014) - Manzanera, Rafael; Jardí, Josefina; Gomila, Xavier; Ramón Pastor, Joan; Ibáñez, Dolores; Gálvez, Glòria; Albertí, Constança; Navarro, Albert; Uris, Joaquín; Pomares, Alicia; López, Lluïsa; Zuazu, Cristina; et al.
Abstract : Purpose: – The authors present the application of the López-Fresno approach in designing an integrated management system (IMS) for an aviation company to the development of an IMS in a government-run organization responsible for the medical evaluation of work disabilities. The purpose of this paper is to share the design process, with the intention of showing that this approach is applicable to other sectors and proposing generalization and applicability strategies to other smaller government entities. Design/methodology/approach: – The study involves two phases. Phase I applies the López-Fresno approach to design a basic IMS-I and ends with a European Foundation for Quality Management (EFQM) evaluation, whose suggestions were taken into consideration for the final design of IMS-II during phase II. The data were obtained from the organization's own functioning. There was a significant degree of personal involvement by the authors, external consultants and members of the management committee in areas ranging from the approach itself to the various components analyzed. Findings: – The approach led to a better use of human and material resources and produced various advances in both internal and external communication and significant progress in employee motivation in their dealings with users and stakeholders. Originality/value: – The study offers guidelines and recommendations for designing an IMS adapted to small, compact, administrative organizations that operate with stakeholders with highly disparate outlooks and interests, with different quality levels, in a context related to competitiveness and economic development.